Nationwide surveillance of pESI-positive Salmonella Infantis ST32 in South Korea: Endemic establishment of a dominant lineage across the broiler production chain, 2020–2023 - Hee-Seung Kang; Md.Sekendar Ali; Bo-Youn Moon; Min Young Kim; Yu-Jeong Hwang; Ji-In Kim; Seung-Chun Park; Jae-Myung Kim; Suk-Kyung Lim (Food Microbiology, 2027)

Accelerated chondrogenic differentiation of stem cells by SOX9 mRNA/dexamethasone-co-loaded lipid nanoparticle for efficient cartilage repair - Ji Sun Park; Hayoung Jeon; Yeeun Lee; Seong Gi Lim; Seo Young Cheon; In-Beom Kim; Hongsoo Choi; Heebeom Koo (Chemical Engineering Journal, 2026)

Development of Korea Air quality observation-based Box model (KAB) - Haeju Lee; Na-Hyeon Kim; Seonghui Lim; Minjoong J. Kim; Minseung Yeo; Min Young Kim; Taehyeon Kim; Ho-Jin Lim; Chang Hoon Jung; Ji Yi Lee; In Ho Song; Gookyoung Heo; et al. (Atmospheric Environment, 2026)

Quadruple co-infection with Mycobacterium tuberculosis complex and M. kansasii in a chronically immunosuppressed cat - Sungyoung Choi; Soo-Nyun Choi; Tak Gyeom Lee; Sungweon Ryoo; Ji-Hoon Kwak; Kun-Woo Kim; Tae In Park; Woo-Jin Song; Eun-Joo Lee; Kyu-Shik Jeong (Veterinary Research Communications, 2026)

Microphysiological system-based respiratory toxicity assessment: recent advances and regulatory perspectives - In Jae Bang; Min-Seok Kim; Yubin Han; Ga Eun Kim; Jung Eun Lim; Ji Yeong Park; Jin Yoo; Young Seo Jang; Beomhee Lee; Minjin Kwak; Soojin Park; Wonjun Jang; et al. (Toxicological Research, 2026)

Petrogenesis of the Coeval High-Mg Diorites and Adakitic Granodiorites in Seolhwa Igneous complex: Insights into the parental melt diversity of early cretaceous magmatism in the Korean Peninsula - Sophia Ji-In Ree; Jung-Woo Park; Sunghwan Im; Sang-Bong Yi; Seon-Gyu Choi; Sung Hi Choi; Jieun Seo; Chang-Whan Oh (Lithos, 2026)

Reassembled yeast vacuoles preserve endothelial viability and barrier integrity in an in vitro blood–brain barrier model - Yoon-Young Hwang; Cho-Im Oh; Jin-Pyo Lee; Su-Min Lee; Dae-Young Park; In-Hwan Oh; Tae-rim Kim; Ok Chan Jeong; Ji-Young Ahn; Yang-Hoon Kim; Jiho Min (Molecular & Cellular Toxicology, 2026)

Genome-scale model-guided microbial engineering for valorization of agricultural waste biomass to poly(3-hydroxybutyrate) - Chae-Rim Jeong; Jaeseong Hwang; Young-Kwon Park; Jae Yong Ryu; Yong Hee Han; Ji Young Jeong; In Min Hwang; Ryeongeun Kim; Jung Eun Yang (Bioresource Technology, 2026)

Functional characterization and enhanced production of extracellular vesicles from lactic acid bacteria using red light-emitting diodes - Su Yeon Park; Hyun Jin Na; In-Geun Jung; Do Yup Lee; Yeong Ji Oh (Biocatalysis and Agricultural Biotechnology, 2026)

Development of Lung Mimics Using Homogeneous Pluripotent Stem Cells in Deep-Well Plate with Antioxidant-Enriched Media for Drug Screening and Infectious Disease Research - In-Su Park; Ji-Young Oh (Tissue Engineering and Regenerative Medicine, 2026)

Characterisation and mechanism of action of the antimicrobial activity of hetero-exopolysaccharide from Lentilactobacillus buchneri KU200793 against Staphylococcus aureus and Listeria monocytogenes - Manoj Kumar Yadav; Ji Hoon Song; Robie Vasquez; Jae Seung Lee; Young-Seo Park; Hyun-Dong Paik; In Ho Kim; Dae-Kyung Kang (Archives of Microbiology, 2026)

Near-infrared light–responsive implantable module integrated into glaucoma drainage device for controlled antifibrotic drug therapy - Chang Hee Min; Young In Shin; Han Bi Ji; Soo Bin Yoon; Yeonseo Kim; Cho Rim Kim; Jae Hoon Han; Min Ji Kim; Myung Ju Kim; Eun Jung Kwon; Young Kook Kim; Ki Ho Park; et al. (Chemical Engineering Journal, 2026)

A Fucose-containing Hetero-exopolysaccharide From Levilactobacillus brevis B151 Exhibits Potent Antimicrobial, Antibiofilm, and Antioxidant Activities - Manoj Kumar Yadav; Remilyn M. Mendoza; Ji Hoon Song; Robie Vasquez; Jae Seung Lee; Yeong-Seo Park; Hyun-Dong Paik; In Ho Kim; Dae‑Kyung Kang (Probiotics and Antimicrobial Proteins, 2026)

Single-atom Cu-N/O aerogel nanozymes with dual enzymatic activities for point-of-care detection of multiple neurotransmitters - Thinh Viet Dang; Hyun Uk Lee; Ji-In Park; Jong-Seong Bae; Moon Il Kim (Chemical Engineering Journal, 2026)

Development of an aptamer-based diagnostic method targeting PRRSV-induced cytopathic effects - In-Hwan Oh; Phat-Loc Nguyen; Dae-Young Park; Jin-Pyo Lee; Woo-Ri Shin; Su-Min Lee; Jiho Min; Ji-Young Ahn; Yang-Hoon Kim (Molecular & Cellular Toxicology, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

Digital-twin tool for a drinking water distribution system using augmented reality and EPANET - Ji-Ye Park; Kwang-Ju Kim; Minhyuk Jeung; In-Su Jang; Jung-Won Yu; Mi-Seon Kang; Hyun-Su Bae; Changyoon Jeong; Sang-Soo Baek (Environmental Modelling & Software, 2026)

Future variability in groundwater-surface water interactions: Implications for streamflow and its components using SWAT-MODFLOW 6 and CMIP 6 projections - Suh-Ho Lee; Hye-Ji Kim; In-Hee Cho; Seong-Sun Lee; Hyemin Park; Youn-Tae Kim; MoonSu Kim; Kang-Kun Lee (Journal of Hydrology, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Genetic mapping of tomato mutants using InDel markers between S. pimpinellifolium and two S. lycopersicum cultivars - Smita Mirsyad Warsadiharja; Shandra Amarillis; Jung Heo; Seunghye Park; Hye-yeong Kang; Yong Jun Kim; Junwoo Lee; Kang Il Cha; Eun Song Lee; Ji In Jang; A-ra Joh; Keunhwa Kim; et al. (Plant Biotechnology Reports, 2025)

First report of Erysiphe lonicerae causing powdery mildew on goldflame honeysuckle (Lonicera × heckrottii) in Korea - Lamiya Abasova; In-Young Choi; Hye-Ryeong Jang; Ji-Hyun Park; Hyeon-Dong Shin (Journal of Plant Pathology, 2025)

3D liver model for assessing immune-mediated hepatotoxicity from biopharmaceutical risks - Mi-lang Kyun; Duhyeon Park; Hyewon Jung; Ji Hyeon Ryu; Inhye Kim; Seo Yule Jeong; Jeongha Kim; Minseong Jo; Ji-In Kwon; Ju-Kang Kim; Dahong Kim; Su A. Park; et al. (Chemical Engineering Journal, 2025)

Assessment of mechanisms and efficiencies for Mn decrease at unit processes in passive treatment facilities for mine drainage - Hye-Lim Kwon; Duk-Min Kim; Seong-Sook Park; Ji-Hye Hong; Ju-In Ko (Environmental Geochemistry and Health, 2025)

Enhanced oral bioavailability of pranlukast by preparing amorphous solid dispersion via hot-melt extrusion - Dong-Hyeon Ha; Eun-Sol Ha; Heejun Park; Seon-Kwang Lee; Ji-Su Jeong; Hui-Taek Kang; Kyu-Tae Kang; In-hwan Baek; Min-Soo Kim (Journal of Pharmaceutical Investigation, 2025)

Holomorph morphology and molecular phylogeny confirm Erysiphe necator var. necator causing powdery mildew on Vitis flexuosa in Korea - Ji-Hyun Park; Lamiya Abasova; In-Young Choi; Hyeon-Dong Shin (Journal of Plant Pathology, 2025)

A novel mechanistic model for diagnosing the general health status of kimchi cabbage using the discrete-pixel data - Sang-Deok Lee; You Jin Lim; Kyung-Hwan Yeo; Oak-Jin Lee; Yun-Soo Choi; Gyu Hyeon Park; Hyejin Lee; Hyo In Yoon; Taeyang Kim; Ji-Hye Moon (Computers and Electronics in Agriculture, 2025)

Study on modulation of inflammation expression by Brassica oleracea L. leaves extract - Jung-Wook Kang; Dan-Hee Yoo; Hyo-Min Kim; Ji-Won Hur; Kyeung-A Kwon; Kyung-Eun Lee; Min-Yeong Kim; Yong-Jun Kwon; Su-Bin Yu; Ju-Hyun Park; In-Chul Lee (Phytochemistry Letters, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Floral development and phenolic compounds production in Agastache rugosa through light regulation - Yun Ji Park; Su Hyeon Lee; Hyo In Yoon; Jai-Eok Park; To Quyen Truong; Je Hyeong Jung; Jung-Seok Yang; Inkyu Park; Sang Min Kim (Planta, 2025)

OsWRKY113 undermines jasmonic acid-dependent immune responses to Fusarium fujikuroi - Yujeong Jeong; Ji In Jang; Eun-Jung Suh; Nam-Jin Chung; Sang Ryeol Park; Seungmin Son (Planta, 2025)

Macluraparishin C Enhances Neuroprotection Against Oxidative Stress-Induced Neurodegeneration by Activating the Antioxidant/MAPK Signaling Pathway - Md Shiblee Sadik Sabuj; Md Sadikul Islam; Md Rashedunnabi Akanda; Joonseok Lee; Ryunhee Kim; Seung Hyun Lee; Ye Ji Kim; Jin Min Oh; Hyeon Gyeong Ro; In-Shik Kim; Dongchoon Ahn; Sang-Youel Park; et al. (Molecular Neurobiology, 2025)

Physiological Effects of Suspended Solids on Venerupis philippinarum and Argopecten irradians - Ha-Jeong Son; Ju-Won Kim; Min-Young Sohn; Chae-yeong Ji; Su Bhin Jeong; In Gu Kim; Jung-Ha Kang; Hee Jeong Kong; Chan-Il Park; Gyoungsik Kang (Fishes, 2025)
Suspended solids are small particles transported in the water column, which can damage marine ecosystems and impair the health of aquatic organisms. This study evaluated the physiological responses of clams (Venerupis philippinarum) and Atlantic Bay scallops (Argopecten irradians) to suspended solid exposure. Four concentrations (100–1000 mg/L) were tested, with a control group maintained at 0 mg/L. At each time point (1, 2, 4, 6, 8, and 12 days), hemolymph samples were collected from five individuals per group to measure GOT, GPT, ALP, and cortisol. Exposure to suspended solids significantly increased these biochemical indicators compared with the control. Quantitative survival analysis showed that Venerupis philippinarum survival declined to 83.3% (25/30) at 500 mg/L and 76.7% (23/30) at 1000 mg/L after 5 days, while the control maintained 100% survival. In Argopecten irradians, survival remained close to 100% in most treatments, with a slight reduction to 83.3% (25/30) at 1000 mg/L. No mortality occurred in the control group without suspended solids, whereas mortality was evident under combined temperature stress and suspended solid exposure. These findings demonstrate that suspended solids induce stress responses in both species, with early mortality in Venerupis philippinarum likely caused by particle adhesion to the gills, leading to reduced respiratory efficiency.

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Dissecting the role of hydrogen pumping by rhenium oxide in enhancing the dehydrogenation of perhydro-dibenzyltoluene on Pt/Al2O3 - Ji Soo Jang; Min-Woo Lee; Seok-Ho Lee; Eun-Suk Jeong; Tae In Park; Kwan-Young Lee (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

First report of Erysiphe aquilegiae causing powdery mildew on Chinese buttercup (Ranunculus cantoniensis) in Korea - In-Young Choi; Lamiya Abasova; Byoung-Ki Choi; Hyeon-Dong Shin; Ji-Hyun Park (Journal of Plant Pathology, 2025)

Improved thermal stability of NbCoSn half-Heusler compounds via Sb doping-induced complementary point defect evolution - Kyuseon Jang; Poulumi Dey; Biswanath Dutta; Hail Park; Ji-Hee Son; Jeong-In Jang; Mohammed Kamran Bhat; Hanhwi Jang; Hyungsub Kim; Jungwoo Choi; Siyuan Zhang; Ruben Bueno Villoro; et al. (Chemical Engineering Journal, 2025)

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Modulating energy band structure of CsPbBr3@TiO2 composites for enhanced photocatalytic and anti-superbacterial performance - Chang-Yeon Kim; Min-Gi Jeon; Artavazd Kirakosyan; Da-Hye Kim; Hea-Jong Chung; Ji-Hyun Lee; Ha-Rim An; Byoungchul Son; Seung Jo Yoo; Sang-Gil Lee; Ji-In Park; Soo Hyeon Kim; et al. (Journal of Water Process Engineering, 2025)

Machine learning-driven discovery of innovative hybrid solid electrolytes for high-performance all-solid-state batteries - Ji-Hwan Kim; Jiwon Sun; Juo Kim; Ji-Min Hong; Seungpyo Kang; Jinyoung Jeong; Eunsong Kim; Deok-Hye Park; Jae-Sung Jang; Jong-Won Lim; Gang-In Lee; Kyoungmin Min; et al. (Chemical Engineering Journal, 2025)

Continuous manufacturing and process analytical technology: focusing on dosage forms with improved solubility and controlled release - Su Hyun Seok; Seung-Dong Yoo; Dong‑Wook Kim; In-Ah Lee; Kyung Hyun Min; Ji-Hyun Kang; Chun-Woong Park; Ju-Young Kim; Eun-Seok Park (Journal of Pharmaceutical Investigation, 2025)

Correction to: PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2025)

Salinity alternation with dark treatment enhances the gel quality and quantity of carrageenan in a red alga, Chondrus crispus - Hye-In Song; Ji-Sook Park; Jang K. Kim (Aquaculture, 2025)

Single oral toxicity assessment and phytochemical analysis of the Ficus erecta Thunb. Leaves extract - Yu Jin Kim; Mee-Young Lee; Hyun Ji Park; Eunjin Sohn; Woo-Young Jeon; Sae-Rom Yoo; In Suk Choi; Joo-Hwan Kim; Soo-Jin Jeong (Toxicon, 2025)

Visualization experiment for characterizing the influence of an open fracture on CO2 behavior in fractured porous media - Seung-Wook Ha; Ji-Young Baek; In-Woo Park; Kang-Kun Lee (Advances in Water Resources, 2025)

A new quantitative method to validate the expression of homoeologous genes in polyploids - Keunhwa Kim; Eun Song Lee; Smita Mirsyad Warsadiharja; Junwoo Lee; Hye-yeong Kang; Ji In Jang; Yu Seon Chae; Soon Ju Park (Plant Biotechnology Reports, 2024)

Revisiting Pseudocercospora puerariicola associated with leaf spot on Pueraria montana var. lobata with morphological and molecular-phylogenetic data in Korea - In-Young Choi; Lamiya Abasova; Ji-Hyun Park; Hyeon-Dong Shin (Journal of Plant Pathology, 2024)

Carboxymethyl cellulose-based rotigotine nanocrystals-loaded hydrogel for increased transdermal delivery with alleviated skin irritation - Jun Soo Park; Jae Hee Seo; Min Young Jeong; In Gyu Yang; Ji Seong Kim; Jin Hwan Kim; Myoung Jin Ho; Sung Giu Jin; Min Koo Choi; Yong Seok Choi; Myung Joo Kang (Carbohydrate Polymers, 2024)

Polyhexamethylene guanidine phosphate induces pyroptosis via reactive oxygen species-regulated mitochondrial dysfunction in bronchial epithelial cells - Jun Young Park; Ji-Hee Kim; Chan Ho Park; Sung-Hwan Kim; In-Hyeon Kim; Won Gil Cho (Toxicology, 2024)

First report of powdery mildew caused by Erysiphe mori on Morus cathayana in Korea - In-Young Choi; Lamiya Abasova; Hyeon-Dong Shin; Ji-Hyun Park (Journal of Plant Pathology, 2024)

Highly visible-light-active sulfur and carbon co-doped TiO2 (SC-TiO2) heterogeneous photocatalysts prepared by underwater discharge plasma - Ha-Rim An; Chaehun Lim; Chung Gi Min; Byoungchul Son; Chang-Yeon Kim; Ji-In Park; Jong Pil Kim; Yesul Jeong; Jiwon Seo; Moonsang Lee; Jihyang Park; Young-Seak Lee; et al. (Chemosphere, 2024)

Dry reforming process using microwave plasma generator with high carbon dioxide conversion efficiency for syngas production - Chang Hyun Cho; Ji Hun Kim; Jong Keun Yang; In Sun Park; Yong-Sup Choi; In Je Kang (Fuel, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

Low-dose-rate gamma radiation aggravates titanium dioxide nanoparticle-induced lung injury in mice - Sohi Kang; Hae-June Lee; Yeonghoon Son; Min Ji Bae; Wol Soon Jo; Jun Hong Park; Sohee Jeong; Changjong Moon; In-Sik Shin; Chang Geun Lee; Joong Sun Kim (Molecular & Cellular Toxicology, 2024)

Distributions of PCDD/Fs, PCBs, and PCNs in coastal sediments collected from major industrial bays in South Korea - Ji-Young Son; Sanjenbam Nirmala Khuman; Min-Kyu Park; Ho-Young Lee; Chul-su Kim; In-Seok Lee; Sung-Deuk Choi (Marine Pollution Bulletin, 2024)

Considering the Chemical Components of Particulate Matter 2.5 for Assessing Its Health Risks to Residents near the Ansan/Siheung and Ulsan Industrial Complexes - Ji-Yun Jung; Shin-Young Park; Jeong-In Jeon; Hye-Won Lee; Sung-Won Yoon; Cheol-Min Lee (Water, Air, & Soil Pollution, 2024)

Solvothermal liquefaction of orange peels into biocrude: An experimental investigation of biocrude yield and energy compositional dependency on process variables - Ishaq Kariim; Ji-Yeon Park; Wajahat Waheed Kazmi; Hulda Swai; In-Gu Lee; Thomas Kivevele (Bioresource Technology, 2024)

Development of an In Vitro Model for Inflammation Mediated Renal Toxicity Using 3D Renal Tubules and Co-Cultured Human Immune Cells - Mi-lang Kyun; Tamina Park; Hyewon Jung; Inhye Kim; Ji-In Kwon; Seo Yule Jeong; Myeongjin Choi; Daeui Park; Yu Bin Lee; Kyoung-Sik Moon (Tissue Engineering and Regenerative Medicine, 2023)

Performance analysis of heat pipe-based passive in-core decay heat removal system for the small modular reactor design with MARS-KS code - Ji Yong Kim; Ye Yeong Park; In Cheol Bang (Annals of Nuclear Energy, 2023)

Efficient MAPbI3-based perovskite solar cells exceeding 21% efficiency via aging treatment - Dae Woo Kim; Young Wook Noh; Jongmin Han; Hye Seung Kim; Chung Hyeon Jang; Ji A. Hong; Sangmi Park; Min Hyeong Lee; Ye In Kim; Myoung Hoon Song (Chemical Engineering Journal, 2023)

Suppression of TBCK enhances TRAIL-mediated apoptosis by causing the inactivation of the akt signaling pathway in human renal carcinoma Caki-1 cells - Cho-Young Park; Ji-Hoon Jang; In-Hwan Song; Joo-Young Kim; Kyung-Oh Doh; Tae-Jin Lee (Genes & Genomics, 2023)

Led-mediated instantaneous pore formation in membranes driven by structural transformation and deprotonation of phospholipids - Hui Bang Cho; Hye Jin Kim; Hye-Ryoung Kim; Sujeong Lee; Ji-In Park; Keun-Hong Park (Chemical Engineering Journal, 2023)

Quantification and health risk assessment of ochratoxin A in dried fruit, spices, and coffee - In Min Hwang; Ji Young Jeong; Boyeon Park; Ji Yeon Choi; Naeem Khan; Nargis Jamila; Bo Ryun Yoon; Jae Sung Kim (Food Additives & Contaminants: Part A, 2023)

Safety concerns regarding impurities in L-Tryptophan associated with eosinophilia myalgia syndrome - Soo Min Ko; Ji-Eun Park; In Kyung Heo; Yong Uk Shin; Yang Hee Kim; Woo-Chan Son (Food and Chemical Toxicology, 2023)

Establishment of a human induced pluripotent stem cell derived alveolar organoid for toxicity assessment - Jooyeon Lee; Hyosin Baek; Jimin Jang; Jaehyun Park; Sang-Ryul Cha; Seok-Ho Hong; Jieun Kim; Jong-Hee Lee; In-Sun Hong; Seung-Jun Wang; Ji Young Lee; Myung Ha Song; et al. (Toxicology in Vitro, 2023)

Biochemical responses and phytoremediation potential of Azolla imbricata (Roxb.) Nakai in water and nutrient media exposed to waste metal cutting fluid along with temperature and humidity stress - Sivakumar Subpiramaniyam; Sung-Chul Hong; Pyong-In Yi; Seong-Ho Jang; Jeong-Min Suh; Eun-Sang Jung; Je-Sung Park; Velmurugan Palanivel; Young-Chae Song; Lae-Hyeon Cho; Young-Hoon Park; Ji-Suk Kim (Journal of Hazardous Materials, 2023)

Chemical and morphological characterization by SEM–EDS of PM2.5 collected during winter in Ulaanbaatar, Mongolia - Ji-In Park; Min Sung Kim; Myoung Yeo; Mira Choi; Ji Yi Lee; Amgalan Natsagdorj; Changhyuk Kim; Mijung Song; Kyoung-Soon Jang (Atmospheric Environment, 2023)

Construction of an underwater plasma and Fenton hybrid system for the rapid oxidation of organic dyes and antibiotics - Soo Hyeon Kim; Jiwon Seo; Yongcheol Hong; Yongwook Shin; Hea-Jong Chung; Ha-Rim An; ChangYeon Kim; Ji-In Park; Hyun Uk Lee (Journal of Water Process Engineering, 2023)

Sargassum horneri and Ascophyllum nodosum extracts enhance thermal tolerance and antioxidant activity of Neopyropia yezoensis - Sol Han; Hye-In Song; Ji-Sook Park; Youn-Jung Kim; Schery Umanzor; Charles Yarish; Jang K. Kim (Journal of Applied Phycology, 2023)

Clean power generation from salinity gradient using reverse electrodialysis technologies: Recent advances, bottlenecks, and future direction - Soryong Chae; Hanki Kim; Jin Gi Hong; Jaewon Jang; Mitsuru Higa; Mohammad Pishnamazi; Ji-Yeon Choi; Ramali Chandula Walgama; Chulsung Bae; In S. Kim; Jin-Soo Park (Chemical Engineering Journal, 2023)

Construction of full-length infectious clones of turnip mosaic virus isolates infecting Perilla frutescens and genetic analysis of recently emerged strains in Korea - Zheng-Xing Song; Su-Jeong Chu; Eun-Young Seo; Wen-Xing Hu; Yong Pyo Lim; Tae-Seon Park; Ji-Soo Park; Jin-Sung Hong; In-Sook Cho; John Hammond; Hyoun-Sub Lim (Archives of Virology, 2022)

Galuteolin, identified in the extract of thymus quinquecostatus flowers, is involved in inhibiting melanin biosynthesis in B16/F10 melanoma cells - Mi-Hee Kim; Bora Kwon; Kwang-Sang Kim; Min-Sook Kim; Min-Ji Kim; Hwa-Jin Kim; Da-In Choi; Miyeon Park; Moosung Kim; Min-Kyu Shin; Seung-Il Jeong; Kang-Yeol Yu; et al. (Natural Product Research, 2021)

The optimal standard protocols for whole-genome sequencing of antibiotic-resistant pathogenic bacteria using third-generation sequencing platforms - Tae-Min La; Ji-hoon Kim; Taesoo Kim; Hong-Jae Lee; Yoonsuk Lee; Hyunjin Shin; Yongjun Song; Gyuhee Ahn; Won Hur; Joong-Bok Lee; Seung-Yong Park; In-Soo Choi; et al. (Molecular & Cellular Toxicology, 2021)

Lactucin induces apoptosis through reactive oxygen species-mediated BCL-2 and CFLARL downregulation in Caki-1 cells - Ji Hoon Jang; Cho-Young Park; Eon-Gi Sung; In-Hwan Song; Joo-Young Kim; Chuleui Jung; Ho-Yong Sohn; Tae-Jin Lee (Genes & Genomics, 2021)

Overexpression of Arabidopsis thaliana blue-light inhibitor of cryptochromes 1 gene alters plant architecture in soybean - Hyun Suk Cho; Yoon Jeong Lee; Hye Jeong Kim; Moon-Young Park; Wan Woo Yeom; Ji Hyeon Song; In Ah Kim; Seong-Hyeon Kim; Jeong-Il Kim; Young-Soo Chung (Plant Biotechnology Reports, 2021)

Transcriptome analysis of primary chicken cells infected with infectious bronchitis virus strain K047-12 isolated in Korea - Rangyeon Lee; Ji Seung Jung; Ji-in Yeo; Hyuk Moo Kwon; Jeongho Park (Archives of Virology, 2021)

Temporal variation of sulfate concentration in PM2.5 and major factors enhancing sulfate concentration in the atmosphere of Seoul, Korea - Na Kyung Kim; In Sun Kim; In Ho Song; Seung Myung Park; Hyung Bae Lim; Yong Pyo Kim; Hye Jung Shin; Ji Yi Lee (Air Quality, Atmosphere & Health, 2021)

First report of powdery mildew caused by Podosphaera sibirica on Veronicastrum sibiricum in Korea - In-Young Choi; Ji-Hyun Park; Bok-Nam Jung; Hyeon-Dong Shin (Journal of Plant Pathology, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Resolvin D3 Promotes Inflammatory Resolution, Neuroprotection, and Functional Recovery After Spinal Cord Injury - Juri Kim; Hari Prasad Joshi; Seung Hun Sheen; Kyoung-Tae Kim; Jae Won Kyung; Hyemin Choi; Ye Won Kim; Su Yeon Kwon; Eun Ji Roh; Un Yong Choi; Seil Sohn; Yong Ho Kim; et al. (Molecular Neurobiology, 2021)

Biological activities and chemical components of Potentilla kleiniana Wight & Arn - Song Hua Xuan; In Ki Hong; Yun Ju Lee; Ji Woong Kim; Soo Nam Park (Natural Product Research, 2020)

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Particle number size distributions generated by different Korean pork cooking methods - Soo Ran Won; In-Keun Shim; Myunghee Kwon; Hyun Ah Ji; Ki-soo Park; Young Sung Ghim (Air Quality, Atmosphere & Health, 2020)

The medicinal mushroom Auricularia auricula - judae (Bull.) extract has antioxidant activity and promotes procollagen biosynthesis in HaCaT cells - Young-Ji Choi; In-Sun Park; Mi-Hee Kim; Bora Kwon; Young-Moo Choo; Seung-Il Jeong; Kang-Yeol Yu; Chung Hyeon Choe; Jiyoung Kim (Natural Product Research, 2019)

Enzymatic synthesis of β-galactosyl fucose using recombinant bifidobacterial β-galactosidase and its prebiotic effect - So-Young Oh; Myeong-Soo Park; Yeong-Geun Lee; Nhan Nguyen Thi; Nam-In Baek; Geun-Eog Ji (Glycoconjugate Journal, 2019)

PRDX6 Inhibits Neurogenesis through Downregulation of WDFY1-Mediated TLR4 Signal - In Jun Yeo; Mi Hee Park; Dong Ju Son; Ji Young Kim; Kyoung Tak Nam; Byung Kook Hyun; So Young Kim; Myung Hee Jung; Min Ji Song; Hyung Ok Chun; Tae Hyung Lee; Sang-Bae Han; et al. (Molecular Neurobiology, 2019)
Impaired neurogenesis has been associated with several brain disorders, such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The role of peroxiredoxin 6 (PRDX6) in neurodegenerative diseases is very controversial. To demonstrate the role of PRDX6 in neurogenesis, we compared the neurogenesis ability of PRDX6-overexpressing transgenic (Tg) mice and wild-type mice and studied the involved molecular mechanisms. We showed that the neurogenesis of neural stem cells (NSCs) and the expression of the marker protein were lower in PRDX6 Tg-mice than in wild-type mice. To determine the factors involved in PRDX6-related neural stem cell impairment, we performed a microarray experiment. We showed that the expression of WDFY1 was dramatically decreased in PRDX6-Tg mice. Moreover, WDFY1 siRNA decreases the differentiation ability of primary neural stem cells. Interestingly, WDFY1 reportedly recruits the signaling adaptor TIR-domain-containing adapter-inducing interferon-β (TRIF) to toll-like receptors (TLRs); thus, we showed the relationship among TLRs, PRDX6, and WDFY1. We showed that TLR4 was dramatically reduced in PRDX6 Tg mice, and reduced TLR4 expression and neurogenesis was reversed by the introduction of WDFY1 plasmid in the neural stem cells from PRDX6 Tg mice. This study indicated that PRDX6 inhibits the neurogenesis of neural precursor cells through TLR4-dependent downregulation of WDFY1 and suggested that the inhibitory effect of PRDX6 on neurogenesis play a role in the development of neurodegenerative diseases in the PRDX6 overexpressing transgenic mice.

Stem Cells Seeded on Multilayered Scaffolds Implanted into an Injured Bladder Rat Model Improves Bladder Function - Kshitiz Raj Shrestha; Seung Hwan Jeon; Ae Ryang Jung; In Gul Kim; Ga Eun Kim; Yong Hyun Park; Soo Hyun Kim; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2019)

Correction to: Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Contribution of Zinc-Dependent Delayed Calcium Influx via TRPC5 in Oxidative Neuronal Death and its Prevention by Novel TRPC Antagonist - Sang Eun Park; Ji Hoon Song; Chansik Hong; Dong Eun Kim; Jee-Won Sul; Tae-Youn Kim; Bo-Ra Seo; Insuk So; Sang-Yeob Kim; Dong-Jun Bae; Mi-Ha Park; Hye Min Lim; et al. (Molecular Neurobiology, 2019)

Development of a PCR test for detection of Xanthomonas campestris pv. raphani - Mehede Hassan Rubel; Mohammad Rashed Hossain; Ujjal Kumar Nath; Sathishkumar Natarajan; Ji-Hee Lee; Hee-Jeong Jung; Hoy-Taek Kim; Jong-In Park; Ill-Sup Nou (Australasian Plant Pathology, 2019)

Differential regional infarction, neuronal loss and gliosis in the gerbil cerebral hemisphere following 30 min of unilateral common carotid artery occlusion - Ji Hyeon Ahn; Minah Song; Hyunjung Kim; Tae-Kyeong Lee; Cheol Woo Park; Young Eun Park; Jae-Chul Lee; Jun Hwi Cho; Young-Myeong Kim; In Koo Hwang; Moo-Ho Won; Joon Ha Park (Metabolic Brain Disease, 2019)

Organic amendment-driven removal and speciation of metals using wormwood in two contrasting soils near an abandoned copper mine - Hee-Myong Ro; Hyo-Jung Choi; Seok-In Yun; Ji-Suk Park (Horticulture, Environment, and Biotechnology, 2018)

Hypoxia-Induced Neuroinflammation and Learning–Memory Impairments in Adult Zebrafish Are Suppressed by Glucosamine - Yunkyoung Lee; Sujeong Lee; Ji-Won Park; Ji-Sun Hwang; Sang-Min Kim; In Kyoon Lyoo; Chang-Joong Lee; Inn-Oc Han (Molecular Neurobiology, 2018)

Effects of CYP2D6 and CYP3A5 genetic polymorphisms on steady-state pharmacokinetics and hemodynamic effects of tamsulosin in humans - Kyoung-Ah Kim; In-Bae Park; Ji-Young Park (European Journal of Clinical Pharmacology, 2018)

Brain ischemic preconditioning protects against moderate, not severe, transient global cerebral ischemic injury - Jae-Chul Lee; Bich-Na Shin; Jeong Hwi Cho; Tae-Kyeong Lee; In Hye Kim; YooHun Noh; Sung-Su Kim; Hyang-Ah Lee; Young-Myeong Kim; Hyeyoung Kim; Jun Hwi Cho; Joon Ha Park; et al. (Metabolic Brain Disease, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants - Jeong In Choi; Song Ji Chae; Jung Min Kim; Jae Chun Choi; Se Jong Park; Hee Ju Choi; Hojae Bae; Hyun Jin Park (Food Additives & Contaminants: Part A, 2018)

Fisetin protects H9c2 cardiomyoblast cells against H2O2-induced apoptosis through Akt and ERK1/2 signaling pathways - Jeong Soo Lee; Ji-Sook Lee; Kyung Jae Cha; Dae-Eun Kim; Daye Lee; Sun Young Jung; Eun-Seok Park; In Sik Kim (Molecular & Cellular Toxicology, 2018)

An ethanol extract from the phaeophyte Undaria pinnatifida improves learning and memory impairment and dendritic spine morphology in hippocampal neurons - Ji-Young Choi; Md. Mohibbullah; In-Sik Park; Il Soo Moon; Yong-Ki Hong (Journal of Applied Phycology, 2018)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Characterization of trichome morphology and aphid resistance in cultivated and wild species of potato - Kwang-Soo Cho; Min Kwon; Ji-Hong Cho; Ju-Sung Im; Young-Eun Park; Su-Young Hong; In-Taek Hwang; Jin-Ho Kang (Horticulture, Environment, and Biotechnology, 2017)

Proteins derived from Prunus armeniaca kernel are possible to cause Immunoglobulin E reactivity in human sera - Kang-Hoon Kim; Ji Young Park; In-Seung Lee; Yumi Kim; Hyeung-Jin Jang (Molecular & Cellular Toxicology, 2017)

Chloroform induces cystein-rich 61, a mediator of collagen homeostasis via early growth response-1 dependent pathway in human skin dermal fibroblasts - Hana Lee; Jae Beom Park; Woo-In Ryu; Ji Hyun Kim; Jung Jin Shin; Sang Wook Son (Molecular & Cellular Toxicology, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

The Association Between Urinary Benzophenone Concentrations and Personal Care Product Use in Korean Adults - Ahra Ko; Hui-Seung Kang; Jae-Hong Park; Ji-Eun Kwon; Gui Im Moon; Myung-Sil Hwang; In Gyun Hwang (Archives of Environmental Contamination and Toxicology, 2016)

Is there a relationship between PPARD T294C/PPARGC1A Gly482Ser variations and physical endurance performance in the Korean population? - Han-Jun Jin; In-Wook Hwang; Ki-Cheol Kim; Hyun-Ik Cho; Tae-Hwan Park; Yun-A Shin; Ho-Seong Lee; Ji-Hyun Hwang; Ah-Ram Kim; Kwang-Hee Lee; Ye-Eun Shin; Ji-Yeon Lee; et al. (Genes & Genomics, 2016)

Oncogenic role of SIRT1 associated with tumor invasion, lymph node metastasis, and poor disease-free survival in triple negative breast cancer - Soo Young Chung; Yoon Yang Jung; In Ae Park; Hyojin Kim; Yul Ri Chung; Ji Young Kim; Soo Young Park; Seock-Ah Im; Kyung-Hun Lee; Hyeong-Gon Moon; Dong-Young Noh; Wonshik Han; et al. (Clinical & Experimental Metastasis, 2016)

Inhibitory effect of snake venom toxin on NF-κB activity prevents human cervical cancer cell growth via increase of death receptor 3 and 5 expression - Hye Lim Lee; Mi Hee Park; Ji Eun Hong; Dae Hwan Kim; Ji Young Kim; Hyen Ok Seo; Sang-Bae Han; Joo Hee Yoon; Won Hyoung Lee; Ho Sueb Song; Ji In Lee; Ung Soo Lee; et al. (Archives of Toxicology, 2016)

LC-ESI-MS/MS analysis of phosphodiesterase-5 inhibitors and their analogues in foods and dietary supplements in Korea - Ji Hye Jeong; Ji Hyun Lee; Hyung Joo Kim; Hyoung Joon Park; In Sun Hwang; Kyoung Moon Han; Chang-Yong Yoon; Sooyeul Cho; Woo Seong Kim (Food Additives & Contaminants Part B-Surveillance, 2016)

Bladder reconstruction using stem cells seeded on multilayered scaffolds in a mucosa preserving partial cystectomy model - Kshitiz Raj Shrestha; Yong Hyun Park; Yong Sun Choi; In Gul Kim; Shuyu Piao; Ae Ryang Jung; Seung Hwan Jeon; Se Heang Oh; Jin Ho Lee; Ji Youl Lee (Tissue Engineering and Regenerative Medicine, 2015)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Different anti-apoptotic effects of house dust mite allergen on eosinophil apoptosis between atopic and non-atopic asthmatic subjects - In Sik Kim; Mi Ae Im; Na Rae Lee; Seung Yeop Baek; Beom Seok Park; Ayoung Gu; Da Hye Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2015)

A novel strain of porcine epidemic diarrhea virus in Vietnamese pigs - Yong Kwan Kim; Seong-In Lim; Ji-Ae Lim; In-Soo Cho; Eun-Hye Park; Van Phan Le; Nguyen Ba Hien; Pham Ngoc Thach; Do Hai Quynh; Tran Quang Vui; Nguyen Trung Tien; Dong-Jun An (Archives of Virology, 2015)

Characterization and miRNA-mediated posttranscriptional regulation of vitelline membrane outer layer protein I in the adult chicken oviduct - Sang In Lee; Mi-Ran Ji; Ye-Jin Jang; Mi-hyang Jeon; Jeom Sun Kim; Jin-Ki Park; Ik-Soo Jeon; Sung June Byun (In Vitro Cellular & Developmental Biology - Animal, 2015)

First report of Bluetongue virus isolation in the Republic of Korea and analysis of the complete coding sequence of the segment 2 gene - Hyun-Ji Seo; Jee-Yong Park; Yun Sang Cho; In-Soo Cho; Jung-Yong Yeh (Virus Genes, 2015)

Polymorphisms of interleukin-31 are associated with anti-CCP levels in females with rheumatoid arthritis - JI-IN YU; YOUNG-RAN PARK; SHIN-SEOK LEE; SOO-CHEON CHAE (Journal of Genetics, 2014)

A new flavonoid glycoside from the root bark of Morus alba L. - Ji-Hae Park; Ye-Jin Jung; Jae-Woo Jung; Sabina Shrestha; Dong Wook Lim; Daeseok Han; Nam-In Baek (Natural Product Research, 2014)

Genome-wide association analysis to identify SNP markers affecting teat numbers in an F2 intercross population between Landrace and Korean native pigs - Jae-Bong Lee; Eun-Ji Jung; Hee-Bok Park; Shil Jin; Dong-Won Seo; Moon-Suck Ko; In-Cheol Cho; Jun-Heon Lee; Hyun-Tae Lim (Molecular Biology Reports, 2014)

Simiduia aestuariiviva sp. nov., a gammaproteobacterium isolated from a tidal flat sediment - Sooyeon Park; Soo-In Kim; Chul-Hyung Kang; Ji-Min Park; Jung-Hoon Yoon (Antonie van Leeuwenhoek, 2014)

Flavonoids from Lindera glauca Blume as low-density lipoprotein oxidation inhibitors - Gyu-Won Huh; Ji-Hae Park; Ji-Hyun Kang; Tae-Sook Jeong; Hee Cheol Kang; Nam-In Baek (Natural Product Research, 2014)

Phenolic components from Rhus parviflora fruits and their inhibitory effects on lipopolysaccharide-induced nitric oxide production in RAW 264.7 macrophages - Sabina Shrestha; Dae-Young Lee; Ji-Hae Park; Jin-Gyeong Cho; Dong-Sung Lee; Bin Li; Youn-Chul Kim; Geum-Soog Kim; Myun-Ho Bang; Nam-In Baek (Natural Product Research, 2013)

3-O-Acetyloleanolic acid exhibits anti-angiogenic effects and induces apoptosis in human umbilical vein endothelial cells - En-Ji Cui; Jeon Hwang-Bo; Jong-Hwa Park; Nam-In Baek; Jiyoung Kim; Seong Gil Hong; In Sik Chung (Biotechnology Letters, 2013)

Natural production of alkane by an easily harvested freshwater cyanobacterium, Phormidium autumnale KNUA026 - Jiwon Chang; Ji Won Hong; Hyunsik Chae; Han Soon Kim; Kyung Mok Park; Kyoung In Lee; Ho-Sung Yoon (Algae, 2013)

Chronological changes in inflammatory cytokines immunoreactivities in the mouse hippocampus after systemic administration of high dosage of tetanus toxin - Bing Chun Yan; Joon Ha Park; In Hye Kim; Bich Na Shin; Ji Hyeon Ahn; Ki-Yeon Yoo; Deuk-Sik Lee; Myong Jo Kim; Il-Jun Kang; Moo-Ho Won (Experimental Brain Research, 2012)

A missense mutation (c.1963A<G) of the complementary component 2 (C2) gene is associated with serum Ca++ concentrations in pigs - Jae-Bong Lee; Chae-Kyoung Yoo; Eun-Ji Jung; Jung-Hye Hwang; Bo-Young Seo; Byeong-Woo Kim; Hyun-Tae Lim; Jung-Gyu Lee; In-Cheol Cho; Hee-Bok Park (Molecular Biology Reports, 2012)

Determination of endocrine disrupting chemicals in water samples by dispersive liquid–liquid microextraction combined with liquid chromatography–fluorescence detection - Yeonsuk Ryu; Jung-In Lee; Jae-Won Moon; Jung-Hyun Kim; Ji-Hwan Park; Su-Yeon Park; Young A. Yoon; Jeongmi Lee (Journal of Pharmaceutical Investigation, 2012)

Expression and immunohistochemical localization of TMEM16A/anoctamin 1, a calcium-activated chloride channel in the mouse cochlea - Ji Hyun Jeon; Jae Woo Park; Jong Woo Lee; Sung Won Jeong; Sang Won Yeo; In-Beom Kim (Cell and Tissue Research, 2011)

A genome-wide association analysis reveals 1p31 and 2p13.3 as susceptibility loci for Kawasaki disease - Jae-Jung Kim; Young Mi Hong; Saejung Sohn; Gi Young Jang; Kee-Soo Ha; Sin Weon Yun; Myung Ki Han; Kyung-Yil Lee; Min Seob Song; Hyoung Doo Lee; Dong Soo Kim; Jong-Eun Lee; et al. (Human Genetics, 2011)

Assessment of Gene Flow from Genetically Modified Anthracnose-Resistant Chili Pepper (Capsicum annuum L.) to a Conventional Crop - Chang-Gi Kim; Dae In Kim; Hyo-Jeong Kim; Ji Eun Park; Bumkyu Lee; Kee Woong Park; Soon-Chun Jeong; Kyung Hwa Choi; Joo Hee An; Kang-Hyun Cho; Young Soon Kim; Hwan Mook Kim (Journal of Plant Biology, 2009)

Detection of gene flow from GM to non-GM watermelon in a field trial - Chang-Gi Kim; Bumkyu Lee; Dae In Kim; Ji Eun Park; Hyo-Jeong Kim; Kee Woong Park; Hoonbok Yi; Soon-Chun Jeong; Won Kee Yoon; Chee Hark Harn; Hwan Mook Kim (Journal of Plant Biology, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Optimum temperature and salinity conditions for growth of green algae Chlorella ellipsoidea and Nannochloris oculata - Sung Hwoan CHO; Sung-Choon JI; Sung Bum HUR; Jeanhee BAE; In-Seok PARK; Young-Chae SONG (Fisheries Science, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

18S rRNA gene sequences and random amplified polymorphic DNA used in discriminating Manchurian trout from other freshwater salmonids - Long-Guo JIN; Ji-Young CHO; Ki-Baek SEONG; Jung-Youn PARK; In-Soo KONG; Yong-Ki HONG (Fisheries Science, 2006)

Monitoring the occurrence of genetically modified soybean and maize around cultivated fields and at a grain receiving port in Korea - Chang-Gi Kim; Hoonbok Yi; Sangkyu Park; Ji Eun Yeon; Do Young Kim; Dae In Kim; Kyu-Hwa Lee; Taek Chang Lee; In Soon Paek; Won Kee Yoon; Soon-Chun Jeong; Hwan Mook Kim (Journal of Plant Biology, 2006)

A procedure for axenic isolation of the marine microalga Isochrysis galbana from heavily contaminated mass cultures - Ji-Young Cho; Jae-Suk Choi; In-Soo Kong; Soo-Il Park; Russell G. Kerr; Yong-Ki Hong (Journal of Applied Phycology, 2002)